Evaluation of Aqueous Flare Intensity in Eyes Undergoing Intravitreal Bevacizumab Therapy to Treat Neovascular Age-Related Macular Degeneration - Dolar-Szczasny, Joanna; Bucolo, Claudio; Zweifel, Sandrine; Carnevali, Adriano; Rejdak, Robert; Załuska, Wojciech; Czarnek-Chudzik, Aleksandra; Toro, Mario Damiano (Frontiers in Pharmacology, 2021)
Purpose: To evaluate the effect of repeated intravitreal bevacizumab injections on blood-aqueous barrier permeability in eyes with neovascular age-related macular degeneration (AMD). Patients and Methods: Forty-eight consecutive patients with neovascular AMD received 3 intravitreal bevacizumab injections (1 mg) every 30–40 days. Subjects were followed for a period of 4 months and were examined at baseline, 1 day and 1 month after each injection. A control group comprised of 19 neovascular AMD patients waiting to begin anti-vascular endothelial growth factor (VEGF) therapy. Anterior chamber (AC) inflammation was evaluated with biomicroscopy and laser flare photometry. Results: None of the subjects treated with bevacizumab had detectable ocular inflammation during follow-up. An analysis for variance (ANOVA) of the mixed-effects model has shown neither an effect between treatment and control group (p=0.921), nor over the time course of the follow-up (p=0.773). Before treatment, median AC inflammation was 6.7 photons/ms (range: 3.5–18.2 photons/ms). One month after the first, second, and third injections, median laser flare was 6.4, 6.8, and 6.6 photons/ms, respectively, none of which were significantly different from baseline (all p > 0.05). Blood-aqueous barrier permeability did not change between injections and was not different from the control group. Conclusions: Inflammation induced by intravitreal bevacizumab was not detected by examination or flare photometry. This suggests that monthly bevacizumab dosing seems to be safe. The absence of AC inflammation could also reflect the known anti-inflammatory properties of anti-VEGF agents.